The application of human umbilical cord blood mononuclear cells in the management of deep partial thickness burn (Faculty of Medicine Universitas Indonesia, 2013)
Background: Wound healing in burn is a complex process and early complete wound closure still enfaces many problems. Application of stem cells is found to be the future method of wound healing. Among the available sources of allogenic stem cells, umbilical cord blood is quite easy to be obtained, has less ethical issue, and contain multipotent stem cells, which are characterized by low immunogenicity. The study aims to evaluate the potential of human umbilical cord blood mononuclear cells (hUCBMNCs) treatment in the management of deep partial thickness burns. Methods: Twenty patients with deep partial thickness burns were treated with topical application of 2 x 107 hUCBMNCs and silver sulfadiazine (SSD) cream on the comparable wound size in the other sites. The treatments were applied for six times in every two consecutive days. Wound surface area was measured with VisitrakÂ® on day 0, 7, and 11. Pain intensity was evaluated using Wong Bakerâs faces scale on each wound dressing change. Histology examination was performed in some samples of collected skin biopsy of the newly re-epithelialized area of hUCBMNCs and SSD-treated wound at the end of treatment. HLA typing is used to evaluate the issue of safety. Wilcoxon signed rank test was used to compare the rate of wound healing. Results: Sixteen patients of hUCBMNCs-treated showed a significant wound closure in faster than SSD-treated; measured on day 7 (p = 0.041) and day 11 (p = 0.021). Number of patients with reduced pain intensity, from approximately scale 3 to 1/0 on day 7 and 11, were higher in hUCBMNCs-treated compared to SSD-treated wound. In spite of the HLA-mismatch, no allergic reaction, rejection, and infection found on hUCBMNCs-treated wound suggested the safety of this therapy. Histology examination found the formation of dermal-epidermal junction and rete ridges equal to the normal skin on hUCBMNCs-treated wounds. Conclusion: hUCBMNCs are effective and safe to promote re-epithelialization in deep partial thickness burns. (Med J Indones. 2013;22:92-9)Keywords:Â Deep partial thickness burn, mononuclear cells, re-epithelialization, umbilical cord blood